Investigating nurse practitioners in the private sector: a theoretically informed research protocol. Issue 11 (10th March 2017) - Adams, Margaret; Gardner, Glenn; Yates, Patsy
Abstract : Aims and objectives: To report a study protocol and the theoretical framework normalisation process theory that informs this protocol for a case study investigation of private sector nurse practitioners. Background: Most research evaluating nurse practitioner service is focused on public, mainly acute care environments where nurse practitioner service is well established with strong structures for governance and sustainability. Conversely, there is lack of clarity in governance for emerging models in the private sector. In a climate of healthcare reform, nurse practitioner service is extending beyond the familiar public health sector. Further research is required to inform knowledge of the practice, operational framework and governance of new nurse practitioner models. Design: The proposed research will use a multiple exploratory case study design to examine private sector nurse practitioner service. Methods: Data collection includes interviews, surveys and audits. A sequential mixed method approach to analysis of each case will be conducted. Findings from within‐case analysis will lead to a meta‐synthesis across all four cases to gain a holistic understanding of the cases under study, private sector nurse practitioner service. Normalisation process theory will be used to guide the research process, specifically coding and analysis of data using theory constructs and the relevant components associated with those constructs. Conclusions: This article provides a blueprint for the research and describes a theoretical framework, normalisation process theory in terms of its flexibility as an analytical framework. Relevance to clinical practice: Consistent with the goals of best research practice, this study protocol will inform the research community in the field of primary health care about emerging research in this field. Publishing a study protocol ensures researcher fidelity to the analysis plan and supports research collaboration across teams.